Vitamin D, autoimmunity and recurrent pregnancy loss: More than an association. (19th June 2018) - Sharif, Kassem; Sharif, Yousra; Watad, Abdulla; Yavne, Yarden; Lichtbroun, Benjamin; Bragazzi, Nicola Luigi; Amital, Howard; Shoenfeld, Yehuda
Abstract : Recurrent pregnancy loss (RPL) affects close to 1% of couples; however, the etiology is known in only about 50% of the cases. Recent studies show that autoimmune dysregulation is a probable cause of RPL, which in some cases may be overlooked. In order for a pregnancy to proceed to term, early modulation of immunologic response is required to induce tolerance to the semi‐allogenic fetus. Certain subsets of both the innate and adaptive immune responses play a role in the induction of fetomaternal tolerance. A relatively predominant T‐cell helper (Th) 2 and T regulatory (Treg) cell population seem to favor a better pregnancy outcome, whereas Th1 and Th17 cell populations appear to have an opposite effect. Lately, the role of vitamin D in the modulation of immune response was established. Vitamin D has been shown to promote a more favorable environment for pregnancy through various mechanisms, such as enhancement of the shift toward Th2 cells and regulation of immune cell differentiation and cytokine secretion. Therefore, it seems that vitamin D deficiency sways the balance toward a worse outcome and may play a part in recurrent pregnancy loss. This review sheds light on the immunologic changes, which occur in early pregnancy and the regulatory role vitamin D has in the maintenance of this delicate balance.